Evaluasi Kesesuaian Pemberian Antibiotik Empiris Terhadap Antibiogram dan Luaran Klinis pada Pasien Pneumonia Dewasa - Mujiyanti Mujiyanti; Dyah Aryani P.; Endang Darmawan; Irma Risdiana (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
The mortality rate for Community-Acquired Pneumonia (CAP) in Indonesia is in the fourth rankand the top ten diseases each year. The main therapeutic principle of CAP is the administration of antibiotics.Improper antibiotic usage can aff ect the success of therapy. The pattern of antibiotics used in hospitals is usually based on clinical and empirical experience, not based on the germ pattern and the sensitivity of antibiotics. The study aims to describe the suitability of empiric antibiotics against the antibiogram profi le and treatment outcomes in inpatients with CAP at PKU Muhammadiyah Gamping Hospital. This study was conducted under the descriptive-analytic observational study design with a retrospective cohort design where the data source came from secondary data, namely the medical records of community pneumonia patients in 2019 and hospital antibiogram data. The data were collected by using the total sampling method. There were 79 community pneumonia patients. The results of the empirical antibiotic suitability test results on antibiograms and clinical outcomes showed that there was no signifi cant relationship between the suitability of empirical antibiotics to the clinical outcome of leukocytes (p = 0.550; RR = 0.725; 95% CI = 0.252-2.086), clinical outcome temperature (p= 0.545; RR = 0.576; 95% CI = 0.049-6.747) and clinical outcome length of stay (p = 0.631; RR = 0.767; CI95= 0.258-2.275). The conclutions there was no signifi cant relationship between the appropriateness of empirical using of antibiotics and antibiogram profi le include leukocyte, temperature and length of stay of the patients (p>0.05).